PENGARUH KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) MELALUI VARIABEL INTERVENING KEPUASAN KERJA DI KANTOR KECAMATAN BATU SOPANG - Verayanti Natalin Saragih; Anthonius Junianto Karsudjono (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2026)
Many factors influence employee job satisfaction, including organizational commitment, work motivation, and Organizational Citizenship Behavior (OCB). In Batu Sopang District, service performance demonstrated quite good results, with 211 documents, or 80%, completed within one working day. Meanwhile, the remaining 52 documents, or 20%, were completed in more than one day.The purpose of this study was to determine and analyze the influence of organizational commitment and work motivation on job satisfaction and Organizational Citizenship Behavior (OCB) of employees at the Batu Sopang District Office.This quantitative study explored the relationship between the independent and dependent variables. Data were collected through questionnaires from 30 respondents and then tested using PLS (Partial Least Squares).The results of the study show that organizational commitment has a significant effect on employee job satisfaction, work motivation has a significant effect on employee job satisfaction, organizational commitment and work motivation have a significant effect on employee Organizational Citizenship Behavior (OCB), organizational commitment has a significant effect on Organizational Citizenship Behavior (OCB) through the intervening variable of job satisfaction in employees at the Batu Sopang District Office